1985
DOI: 10.1128/jb.164.1.155-164.1985
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis citB gene is regulated synergistically by glucose and glutamine

Abstract: The activity of aconitase in Bacillus subtilis is greatly reduced in cells cultured in media containing rapidly metabolized carbon sources (e.g., glucose). Thus, expression of this enzyme appears to be subject to a form of catabolite repression. Since the product of the citB gene of B. subtilis is required for aconitase activity, we cloned the wild-type allele of this gene and used this DNA as a probe for transcription of citB in cells grown in various media. The steady-state level of RNA that hybridized to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(17 citation statements)
references
References 47 publications
(64 reference statements)
2
14
0
1
Order By: Relevance
“…In contrast to glycolytic enzymes, TCA cycle enzymes are repressed at a high glucose concentration in the presence of glutamate. The proteomic approach provided an overall view on the synthesis of almost all TCA cycle enzymes and was in good agreement with previous reports on enzyme activities and transcription of TCA cycle genes (15,23,34). Differential repression efficiency, suggesting a fine-tuning of expression, was described for citZ and citB, which are more strongly repressed than citC (23) (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to glycolytic enzymes, TCA cycle enzymes are repressed at a high glucose concentration in the presence of glutamate. The proteomic approach provided an overall view on the synthesis of almost all TCA cycle enzymes and was in good agreement with previous reports on enzyme activities and transcription of TCA cycle genes (15,23,34). Differential repression efficiency, suggesting a fine-tuning of expression, was described for citZ and citB, which are more strongly repressed than citC (23) (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Transcriptional regulation of citA and citZ in response to different carbon sources. The enzyme activities of aconitase and citrate synthase and the transcription of the aconitase gene (citB) are synergistically repressed by glucose and glutamate (10,26). As shown in Table 2, we found that expression of citA-lacZ was more than 6-fold lower when glucose was the sole carbon source than when succinate was the sole carbon source.…”
Section: Fig 4 (A)mentioning
confidence: 74%
“…Regulation of the citB gene has been studied in detail and found to involve several mechanisms of transcriptional control (5, 6). In defined medium, citB transcription is synergistically repressed by glucose and glutamate, but it is highly derepressed in a medium with citrate as the sole carbon source (26). This repression has been associated with a region of dyad symmetry upstream of the promoter region (5,6).…”
mentioning
confidence: 99%
“…B. subtilis cells grown overnight on DS (Difco sporulation) agar medium were used to inoculate 2ϫ YT (yeast extract-tryptone) liquid medium (12) supplemented with 1% glucose and 20 mM phosphate buffer (pH 7.0), which contained either 0.2% KNO 3 or 10 mM KNO 2 , to an optical density at 600 nm of 0.02. Alternatively, cells grown aerobically overnight in TSS liquid medium (18) with 0.2% NH 4 Cl were used to inoculate TSS medium containing 0.2% KNO 3 with or without 0.2% NH 4 Cl. Anaerobic growth of cultures was carried out as described previously (16).…”
Section: Methodsmentioning
confidence: 99%